The little black book of decision making making complex decisions with confidence in a fast-moving world - Nicholas, Michael 1962- (Ascent Audio, 2022)
The decisions we make every day-frequently automatic and incredibly fast-impact every area of our lives. The Little Black Book of Decision Making delves into the cognition behind decision making, guiding you through the different ways your mind approaches various scenarios. You'll learn to notice that decision making is a matter of balance between your rational side and your intuition-the trick is in honing your intuition to steer you down the right path. Pure reasoning cannot provide all of the answers, and relying solely on intuition could prove catastrophic in business. There must be a balance between the two, and the proportions may change with each situation. This book helps you quickly pinpoint the right mix of logic and "gut feeling," and use it to find the best possible solution. You'll learn how to: balance logic and intuition in your decision making approach; avoid traps set by the mind's inherent bias; understand the cognitive process of decision making; and sharpen your professional judgement in any situation. Decision making is the primary difference between organizations that lead and those that struggle. The Little Black Book of Decision Making helps you uncover errors in thinking before they become errors in judgment